Approximate seismic performance of full and partial self-centering systems based on spectral analysis of SDOF systems. (March 2022) - Zhang, Ruibin; Qiu, Canxing; Huang, Linting; Jia, Junfeng
Abstract: This paper presents a performance evaluation of full and 'partial' self-centering (SC) systems based on spectral analysis of Single Degree of Freedom (SDOF) systems. The primary objectives are to quantify the structural performances of the full and 'partial' SC systems, with a wide spectrum of structural parameters under near-fault (NF) and far-field (FF) earthquakes, and to assess the accuracy of the prediction models derived from SDOF analysis to approximate the seismic performances of multi-story frame buildings. More than 1.45 million statistical response results are processed and discussed. Among other important findings, it is shown that 'partial' SC systems appear to be a desirable option that could control the acceleration and residual displacement responses without inducing a notable increase in the maximum displacement. Based on the available data, two sets of prediction models about the inelastic displacement demand and residual displacement response are proposed. Finally, the accuracy of the prediction models to approximate the seismic performances of multi-story frame buildings is investigated by the comparison of the responses computed from a series of braced frames with various parameters and that calculated from prediction models. The results imply that the prediction models from SDOF analysis are capable of predicting the seismic performances of the corresponding multi-story frame buildings.